2005
DOI: 10.1002/14651858.cd001717.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Depot perphenazine decanoate and enanthate for schizophrenia

Abstract: Depot perphenazine decanoate and enanthate for schizophrenia (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Reviews on second-generation antipsychotic or FGA depots (eg, bromperidol decanoate, haloperidol depot, risperidone depot, and fluphenazine decanoate) versus oral antipsychotic drugs and placebo indicated that patients with FGA depots had few relapses and fewer oral medications, even though the difference did not reach statistical significance 9496. Together with similar levels of adverse effects found in depot medications, it was also difficult to conclude that a particular depot was no better than any other depot or oral medication 96. Despite showing similar clinical efficacy between oral and depot medications, depot injections can avoid frequent regular administration of and nonadherence to oral medication, rendering them more desirable for maintenance or compliance therapy.…”
Section: Patterns In Medication Use: Mono- and Polypharmacymentioning
confidence: 99%
“…Reviews on second-generation antipsychotic or FGA depots (eg, bromperidol decanoate, haloperidol depot, risperidone depot, and fluphenazine decanoate) versus oral antipsychotic drugs and placebo indicated that patients with FGA depots had few relapses and fewer oral medications, even though the difference did not reach statistical significance 9496. Together with similar levels of adverse effects found in depot medications, it was also difficult to conclude that a particular depot was no better than any other depot or oral medication 96. Despite showing similar clinical efficacy between oral and depot medications, depot injections can avoid frequent regular administration of and nonadherence to oral medication, rendering them more desirable for maintenance or compliance therapy.…”
Section: Patterns In Medication Use: Mono- and Polypharmacymentioning
confidence: 99%